Speech recognition as a function of the number of electrodes used in the SPEAK cochlear implant speech processor. - Fishman KE; Shannon RV; Slattery WH (Journal of Speech, Language & Hearing Research, 1997)
Speech recognition was measured in listeners with the Nucleus-22 SPEAK speech processing strategy as a function of the number of electrodes. Speech stimuli were analyzed into 20 frequency bands and processed according to the usual SPEAK processing strategy. In the normal clinical processor each electrode is assigned to represent the output of one filter. To create reduced-electrode processors the output of several adjacent filters were directed to a single electrode, resulting in processors with 1, 2, 4, 7, 10, and 20 electrodes. The overall spectral bandwidth was preserved, but the number of active electrodes was progressively reduced. After a 2-day period of adjustment to each processor, speech recognition performance was measured on medial consonants, vowels, monosyllabic words, and sentences. Performance with a single electrode processor was poor in all listeners, and average performance increased dramatically on all test materials as the number of electrodes was increased from 1 to 4. No differences in average performance were observed on any test in the 7-, 10-, and 20-electrode conditions. On sentence and consonant tests there was no difference between average performance with the 4-electrode and 20-electrode processors. This pattern of results suggests that cochlear implant listeners are not able to make full use of the spectral information on all 20 electrodes. Further research is necessary to understand the reasons for this limitation and to understand how to increase the amount of spectral information in speech received by implanted listeners.